Role of Repertory in Constitutional Prescribing (Homoeopathy for All, 2026)
Homeopathy emphasizes individu alization through constitutional pre scribing, where treatment is guided  by the totality of physical, mental, and  emotional symptoms. The repertory  serves as a systematic bridge between  case taking and Materia Medica, en abling logical remedy selection. This  article explores the philosophical and  clinical role of the repertory in consti tutional prescribing, its evolution, ap plications in chronic cases, and limita tions in modern practice.
Keywords: constitutional; chronic; repertory; homeopathic